Mewujudkan Pelayanan Publik Berkualitas Melalui Penguatan Etika Birokrasi - Suparno Suparno (Universitas 17 Agustus 1945, 2025)
This study analyzes the strengthening of bureaucratic ethics to realize quality public services in Indonesia using a descriptive narrative method by triangulating data from 40 speakers, policy documentation, and literature studies. The findings show that the implementation of bureaucratic ethics still faces a gap between formal norms and field practice, with an average community satisfaction index of 75.6. Five main factors influence effectiveness: transformational leadership, oversight and sanction systems, organizational culture, HR competencies, and technology support. The study proves a positive correlation between strengthening bureaucratic ethics and improving service quality, where units with high ethical implementation show a 15-20% higher satisfaction index. The main challenges include the resistance of the bureaucratic culture, weak reward and punishment, and lack of systematic capacity building. Strategies to strengthen ethics include: ethical leadership, reform of the reward and punishment system, digitization of services, sustainable capacity building, and strengthening supervision. The theoretical implications contribute to the integration of Weber's ethical concepts, New Public Service, and good governance in the Indonesian context. The practical implications provide a blueprint for bureaucratic reform through five comprehensive strategies that can be implemented in stages to achieve the 2025 world-class public service target.